Daily diurnal temperature range associated with emergency ambulance calls: a nine-year time-series study - Guo, Chaohui; Cai, Keke; Chen, Gao; Wang, Jin; Zeng, Jie; Huang, Xiaoqing; Deng, Mengling (Frontiers in Public Health, 2024)
Background: Diurnal temperature range (DTR) is associated with the increased risk of morbidity and mortality. However, the relationship between DTR and emergency ambulance calls (EACs), which more accurately and immediately reflect the health impacts of temperature changes, remains underexplored in China.We collected daily data on EACs and meteorological factors from 2009 to 2017 in Guangzhou, China. DTR, representing the temperature range within a day, was calculated by subtracting the minimum temperature from the maximum temperature for each day. Generalized additive models were used to estimate the association between DTR and EACs for all-cause, cardiovascular diseases, and respiratory diseases. Additionally, subgroup and sensitivity analyses were conducted in our study.We found significant associations between daily DTR and EACs. The excess risks (ERs) were 0.47% (95% CI: 0.14%, 0.81%) for all-cause EACs, 0.94% (95% CI: 0.46%, 1.43%) for cardiovascular-related EACs, and 1.31% (95% CI: 0.76%, 1.86%) for respiratory -related EACs at lag01, respectively. Subgroup analyses indicated that these associations were notably stronger among the older, males, and during the warm season. Specifically, there was an increase of 1.16% (95% CI: 0.59%, 1.74%) in cardiovascular-related EACs among the elderly, compared to 0.45% (95% CI: -0.21%, 1.12%) among those younger than 65 years. Among males, the increase was 1.39% (95% CI: 0.79%, 1.99%), compared to 0.13% (95% CI: -0.53%, 0.79%) among females. During the warm season, the increase was 1.53% (95% CI: 0.74%, 2.34%), compared to 0.75% (95% CI: 0.14%, 1.37%) during the cold season.Conclusions: DTR might increase the risk of daily all-cause, cardiovascular-related, and respiratory-related EACs in Guangzhou, China. The associations were particularly strong among older adults, males, and during the warm season.Implementing public health policies is essential to mitigate the adverse health effects of DTR.